Snow effects on brash ice and level ice growth - Vasiola Zhaka; Robert Bridges; Kaj Riska; Jonny Nilimaa; Andrzej Cwirzen (Journal of Glaciology)
Brash ice formation and accumulation occur at a faster rate in ship channels, harbours and turning areas compared to the surrounding level ice. Accurate prediction of brash ice thickness plays an important role in addressing operational challenges and optimisation of ice management strategies. This study enhances existing brash ice growth models by considering the effects of snow and accounting for brash ice expulsion towards the sides of ship channels at each passage. To validate the influence of these critical factors on brash ice thickness, three distinct ship channels located in the Bay of Bothnia, Luleå, Sweden, were investigated. For two test channels formed for study purposes, the slower growth rate of brash ice caused by snow insulation was more prominent than the brash ice growth acceleration caused by the snow–slush–snow ice transformation. In the third channel characterised by frequent navigation, the transformation of slush into snow ice played a more substantial role than snow insulation. In both test channels, the brash ice growth model performed optimally, assuming a 10% expulsion of brash ice sideways at each vessel passage. In the third, wider and more frequently navigated channel, a 1.2% brash ice expelling coefficient predicted well the measured brash ice thicknesses.